2015
DOI: 10.1080/00140139.2015.1031191
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between work related musculoskeletal disorders and slips, trips and falls

Abstract: Most occupational risks manifest themselves through movements performed at work, for example musculoskeletal disorders, slips, trips and falls. Research focusing on such risks often differentiates diseases from accidents. All these risks prove to be diffuse, widespread, emergent and devoid of an external harmful hazard, when analysed through their common vector, i.e. through the movements manifesting them. These characteristics have a strong impact on risk perception and on approaches necessary to ensure susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…It is notable that slipping has been a particular area of attention, forming a large part of the discussions at STF symposia over the years, for example, at the Liberty Mutual Research Institute for Safety international symposium on the measurement of slipperiness (Courtney et al 2001a). Some researchers have, however, suggested that use of the ‘slips, trips and falls’ terminology and the tendency to focus on slipping fail to give sufficient recognition to other important causes of injuries on level surfaces involving loss of balance (Lortie and Rizzo 1999) or movement disturbance (Leclercq, Monteau, and Cuny 2010; Leclercq et al 2014; Leclercq et al 2015). …”
Section: Definitions and Scopementioning
confidence: 99%
See 2 more Smart Citations
“…It is notable that slipping has been a particular area of attention, forming a large part of the discussions at STF symposia over the years, for example, at the Liberty Mutual Research Institute for Safety international symposium on the measurement of slipperiness (Courtney et al 2001a). Some researchers have, however, suggested that use of the ‘slips, trips and falls’ terminology and the tendency to focus on slipping fail to give sufficient recognition to other important causes of injuries on level surfaces involving loss of balance (Lortie and Rizzo 1999) or movement disturbance (Leclercq, Monteau, and Cuny 2010; Leclercq et al 2014; Leclercq et al 2015). …”
Section: Definitions and Scopementioning
confidence: 99%
“…stress, motivation). A comprehensive understanding of balance and movement control in occupational situations requires consideration of not only the biomechanics of movement, but also the cognitive, psychological and organisational aspects (Leclercq et al 2015). Indeed, displacements and, more generally, the movements performed at work are subjected to continuous adjustment of the required task as well as individual, organisational and environmental constraints.…”
Section: Organisational Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicated a balance should be established between defended and resilience-based conceptions of health and safety (Leclercq, Cuny-Guerrier, Gaudez & Aublet-Cuvelier, 2015). As the majority of musculoskeletal injuries manifest themselves through slips, trips and falls, these events have a strong impact on risk perception and on approaches necessary to ensure sustainable prevention.…”
mentioning
confidence: 99%
“…As the majority of musculoskeletal injuries manifest themselves through slips, trips and falls, these events have a strong impact on risk perception and on approaches necessary to ensure sustainable prevention. Research should also be extended to enhance an indepth understanding of controls impacting worker movements when performing a task, while safeguarding health and safety (Leclercq, Cuny-Guerrier, Gaudez & Aublet-Cuvelier, 2015). It is evident that a greater resilience possibly allows for a decrease in these events or a greater ability to cope with the events.…”
mentioning
confidence: 99%